Dietary of Lactobacillus paracasei and Bifidobacterium longum improve nonspecific immune responses, growth performance, and resistance against Vibrio parahaemolyticus in Penaeus vannamei. Issue 128 (September 2022) - Huang, Huai-Ting; Hu, Yeh-Fang; Lee, Bao-Hong; Huang, Chih-Yang; Lin, Yu-Ru; Huang, Shu-Ning; Chen, Yin-Yu; Chang, Jui-Jen; Nan, Fan-Hua
Abstract: This study investigated the effects of two probiotics, namely Lactobacillus paracasei and Bifidobacterium longum, as feed additives on growth performance, nonspecific immunity, immune-related gene expression, and disease resistance against Vibrio parahaemolyticus in Penaeus vannamei . The experimental diets were prepared using L. paracasei and B. longum at concentrations of 10 5 and 10 7  CFU/g; these diets were referred to as P5, P7, B5, and B7. After 8 weeks of the diets, regarding growth performance, the B7 group showed the highest weight gain rate (890.34 ± 103.65%), special growth rate (4.08 ± 0.19%), and feed conversion rate (1.52 ± 0.19%) compared with the other groups. Moreover, the total hemocyte counts were significantly increased ( p  < 0.05) in the P7 groups on day 14 during the 28-day feeding trial. The phagocytosis rate in all experimental groups was increased on day 14 and was persistently significantly activated to day 21, especially in the P7 and B5 group. The phagocytic index of the P7 group showed a significant increase on day 14 and persistent activation to day 21. In the analysis of respiratory burst activity and phenoloxidase activity, the P7 and B5 groups showed a significant increase on day 7 and persistent activation to day 21. The expression level of the immune-related genes of superoxide dismutase, clotting protein, Penaeidin2, Penaeidin3, Penaeidin4, anti-LPS factor, crustin, and lysozyme was significantly increased in the experimental groups, especially in the P7 group. Furthermore, the optimum conditions of feed additives were determined in challenge trials conducted using P7 and B5. Shrimps fed P7 and B5 showed an increased survival rate (72.73% and 66.67%) after the V. parahaemolyticus challenge. In sum, the results revealed that B. longum, as a feed additive at 10 7  CFU/g, enhanced growth performance. L. paracasei at 10 7  CFU/g and B. longum at 10 5  CFU/g can enhance nonspecific immune responses and immune-related gene expression, and 10 7  CFU/g L. paracasei has the highest resistance ability for V. parahaemolyticus . Thus, dietary supplementation with L. paracasei and B. longum may be a valuable approach in white shrimp aquaculture. Highlights: Dietary of 10 7  CFU/g Bifidobacterium longum improves the growth performance of shrimp after 56 days of feeding. The dietary additives of Lactobacillus paracasei and Bifidobacterium longum increase shrimp immunity. Dietary of Lactobacillus paracasei and Bifidobacterium longum increase shrimp resistance against V. parahaemolyticus.